Implementation of real time three phase balanced voltage sag generator 1 kVA: Using microcontroller and PC control - Boonmee C. (2014)
A type three-phase voltage sag generator with real time control is proposed for testing equipment, small power application, such as adjustable-speed drives (ASDs), contactors, relays, programmable logic-controller (PLC),and personal computers (PCs), etc. The generating system consists of a 1-kVA synchronous generator, a phase-control ac-dc converter, a constant speed prime-mover. Additional microcontroller and visual basic (VB) software control functions are implemented with a dc voltage-controlled converter in field-winding circuit for regulating the three-phase voltage sag and monitor the system under test. The capabilities of the sag generator were experimentally tested on a standard type-A sag. It is composed of balance three-phase system under various sag conditions. The proposed approach can be easily tested install equipment to ensure that the equipment meets agreed-upon capabilities. © 2009 SICE.